2011
DOI: 10.1587/transinf.e94.d.1153
|View full text |Cite
|
Sign up to set email alerts
|

Shaka: User Movement Estimation Considering Reliability, Power Saving, and Latency Using Mobile Phone

Abstract: SUMMARYThis paper proposes a method for using an accelerometer, microphone, and GPS in a mobile phone to recognize the movement of the user. Past attempts at identifying the movement associated with riding on a bicycle, train, bus or car and common human movements like standing still, walking or running have had problems with poor accuracy due to factors such as sudden changes in vibration or times when the vibrations resembled those for other types of movement. Moreover, previous methods have had problems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We consider a user’s lifelog to be an individual’s behavior or information observed by a smartphone alone (i.e., without any other special devices). Various studies have focused on lifelogs observed by smartphones (Kobayashi et al 2011; Kwapisz et al 2010; Lee and Cho 2011). In these studies, systems inferred the user’s movement states by using analysis and classification of values observed via a three-dimensional accelerometer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider a user’s lifelog to be an individual’s behavior or information observed by a smartphone alone (i.e., without any other special devices). Various studies have focused on lifelogs observed by smartphones (Kobayashi et al 2011; Kwapisz et al 2010; Lee and Cho 2011). In these studies, systems inferred the user’s movement states by using analysis and classification of values observed via a three-dimensional accelerometer.…”
Section: Related Workmentioning
confidence: 99%
“…In these studies, systems inferred the user’s movement states by using analysis and classification of values observed via a three-dimensional accelerometer. In particular, in Kobayashi et al (2011), successfully inferred how a user moves, including walking, running, riding a bicycle, stopping, driving a car, riding a bus, and riding a train. Further, we can also observe a user’s state via new activity recognition APIs on Android by Google.…”
Section: Related Workmentioning
confidence: 99%
“…A location that is valuable from educational aspects, and is also a matter of learners' interest (e.g., region (5,8)). A location where learning occurs as educators expect.…”
Section: Pattern 1: a Location Where Learners Were Interested And Edumentioning
confidence: 99%
“…This has recently been extended to the ability of consumer devices such as mobile phones to sense behaviors [5,8]. For example, by recognizing "slipping on a floor" [14], it is possible to estimate a dangerous situation caused by careless behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in machine learning and deep learning have enabled us to infer many things, such as the activity of the user of the sensor device, from information obtained from sensors [1], [2]. We can expect that the improvement in identification and prediction based on sensed data contributes to many things.…”
Section: Introductionmentioning
confidence: 99%